Securing Financial Information in the Digital Age: An Overview of Cybersecurity Threat Evaluation in Banking Systems - Al Mahmud, Md Abdullah; mou, Jannatul Ferdous; Zaman, Al Modabbir; Dhar, Sweety Rani; Debnath, Anupom; Hassan, Mahafuj; Sharmin, Sadia (Journal of Ecohumanism, 2025)
Financial information, especially in banking systems, requires robust security measures in the increasingly digital world. As technology evolves constantly, security threats also change, which highlights the need for a strong cybersecurity posture. In recent years, banks have been directly affected. Banks are susceptible to a variety of cyberattacks, such as ransomware attacks, DDOS assaults, phishing attacks, and malware attacks. It has been proposed in this paper how to improve financial system security by sharing real-life case studies and research. It includes a range of industries, such as banks, real estate companies, and investment or insurance corporations. The study identified banking regions that are more vulnerable to cyberattacks and ensured the modification and development of cybersecurity protocols. New researchers and those seeking to become deeply involved in cybersecurity in banking systems may find this material helpful as a guide.